A rare case of IgG4-related disease masquerading as periurethral malignancy and review of the literature - Zeng, Zhiru; Gao, Shasha; Lu, Xiaoyong (Frontiers in Immunology, 2023)
Immunoglobulin G4-related disease (IgG4-RD) is an immune-mediated fibroinflammatory disease that typically manifests as mass lesions affecting almost any organ including the pancreas, lacrimal and salivary glands, liver, lung and kidney. However, IgG4-RD with urethra involvement is scarce. We describe a rare case of IgG4-RD involving the urethra mimicking urethral carcinoma and review the published literature. A 64-years-old female presented with progressive dysuria for more than 2 months. Pelvic gadolinium-enhanced magnetic resonance imaging revealed a huge mass encasing the urethra which showed obvious enhancement in the arterial phase. And contrast-enhanced ultrasound showed that the entire mass was heterogeneously enhanced and displayed a fast-forward and fast-out pattern, which was highly suggestive of malignant tumor. The diagnosis of IgG4-RD was finally established by ultrasound-guided transvaginal mass needle biopsy. The patient was treated with methylprednisolone and cyclophosphamide and dysuria disappeared in the first week of therapy. She has been followed up in our clinic for 1 year without recurrence. The diagnosis of IgG4-RD should be considered in the differential diagnosis of a periurethral mass. Ultrasound-guided transvaginal mass needle biopsy is a safe and well-established tissue sampling method and should be performed in order to avoid unnecessary surgery.